Pemberdayaan Masyarakat Pemula (PMP) Peningkatan Kompetensi Pendidik Dalam Pengembangan Perangkat Assessment of Learning Berbasis Digital (ASLIBIDAL) di Sekolah Menengah Atas Kota Surakarta - Ratna Herawati, Ratna Herawati; Kardha, Dessyana; Rachmatullah, Robby; Mairina, Upik (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Learning as a process of organizing the environment around students might meet the National Education Standards. Most educators in Surakarta City had minimal understanding of the assessment of learning outcomes. How was the technique of preparing the right assessment tool in measuring student learning achievement? Based on the situation analysis, the partner's problems were found, including the lack of understanding of educators in the form and technique of preparing appropriate assessment tools, as well as the limited ability of educators to translate assessment techniques into digital form. The proposer's solution was through training, namely first training, designing the preparation of good item items, and providing strategies for composing good item items by paying attention to validity, level of difficulty, discriminating power, and reliability. The second training is monitoring the preparation of item items as well as strengthening the concepts and skills of item analysis techniques as well as assessment tool techniques with the assistance of digital media. The result of the implementation was that the activities run in an orderly manner according to the plan and according to the targets set. From this activity, it could be concluded that there was an increase in the competence of educators in developing digital-based assessments of learning tools after being given training.